The Bible guide - Old Testament - Knowles, Andrew, 1946- (Lion Scholar, 2020)
Hailed as a "classic reference book" by The Right Reverend James Jones, former Bishop of Liverpool, The Old Testament Guide provides readers with a complete all-in-one journey through the books of the Old Testament. Easy to read and navigate, this volume explores, explains, and brings to life the history, stories, cultures, and messages of each book. The accessibility of Andrew Knowles' writing demystifies and contextualises many aspects of the Scriptures, and deepens our understanding of their principles, doctrine, and messages for us today. Interspersed with boxed features that highlight key events, places, people and biblical passages, The Old Testament Guide is an ideal introduction for new scholars and interested readers alike who have little or no grounding in the subject.